A Modular In Vitro Platform for the Production of Terpenes and Polyketides from CO2. Issue 30 (3rd June 2021) - Sundaram, Srividhya; Diehl, Christoph; Cortina, Niña Socorro; Bamberger, Jan; Paczia, Nicole; Erb, Tobias J.
Abstract: A long‐term goal in realizing a sustainable biocatalysis and organic synthesis is the direct use of the greenhouse gas CO2 as feedstock for the production of bulk and fine chemicals, such as pharmaceuticals, fragrances and food additives. Here we developed a modular in vitro platform for the continuous conversion of CO2 into complex multi‐carbon compounds, such as monoterpenes (C10 ), sesquiterpenes (C15 ) and polyketides. Combining natural and synthetic metabolic pathway modules, we established a route from CO2 into the key intermediates acetyl‐ and malonyl‐CoA, which can be subsequently diversified through the action of different terpene and polyketide synthases. Our proof‐of‐principle study demonstrates the simultaneous operation of different metabolic modules comprising of up to 29 enzymes in one pot, which paves the way for developing and optimizing synthesis routes for the generation of complex CO2 ‐based chemicals in the future. Abstract : Coupling of a synthetic CO2 ‐fixing cycle and a natural glyoxylate assimilation cycle with different biosynthetic pathways enables the sustainable production of terpenes and polyketides. Demonstration of this modular, multi‐enzyme in vitro platform sets the stage for a diversified synthesis of pharmaceuticals and commodity chemicals directly from CO2 .